2017
DOI: 10.1016/j.gpb.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Lirex: A Package for Identification of Long Inverted Repeats in Genomes

Abstract: Long inverted repeats (LIRs) are evolutionarily and functionally important structures in genomes because of their involvement in RNA interference, DNA recombination, and gene duplication. Identification of LIRs is highly complicated when mismatches and indels between the repeats are permitted. Long inverted repeat explorer (Lirex) was developed and introduced in this report. Written in Java, Lirex provides a user-friendly interface and allows users to specify LIR searching criteria, such as length of the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Interestingly, they found that, in multiple cases, palindromes which happen to be near genes involved in breast carcinogenesis were among those which differed the most in cancer compared to normal cell genomes. Additionally, several other groups worked on palindrome-counting algorithms which are publicly available [ 78 , 79 ]. Moreover, efforts are being made to overcome other obstacles in identifying DNA palindromes in genomes.…”
Section: Dna Palindromes In the Human Genomementioning
confidence: 99%
“…Interestingly, they found that, in multiple cases, palindromes which happen to be near genes involved in breast carcinogenesis were among those which differed the most in cancer compared to normal cell genomes. Additionally, several other groups worked on palindrome-counting algorithms which are publicly available [ 78 , 79 ]. Moreover, efforts are being made to overcome other obstacles in identifying DNA palindromes in genomes.…”
Section: Dna Palindromes In the Human Genomementioning
confidence: 99%
“…We tested several tools including detectIR ( 25 ), findIR ( 26 ), Inverted Repeats Finder (IRF) ( 20 ) and Lirex ( 27 ) to identify LIRs, and found that IRF is the only tool that was able to identify LIRs with imperfectly matched arms longer than 600 bp. On the contrary, detectIR and findIR were used to identify inverted repeats shorter than 100 nt, developed based on the commercial software MATLAB ( 25 , 26 ).…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…On the contrary, detectIR and findIR were used to identify inverted repeats shorter than 100 nt, developed based on the commercial software MATLAB ( 25 , 26 ). Lirex was able to identify LIRs with long internal loops, but failed to identify LIRs with long arms harboring multiple mismatches and indels between each other ( 27 ). In reality, growing evidence shows that the 3.1-kb LIR reported in Drosophila ( 5 ) as well as the 15 012-bp and 3013-bp LIRs reported in rice ( 10 ) can only be identified by IRF.…”
Section: Data Collection and Methodsmentioning
confidence: 99%